Socio-demographic Characteristics of Patients with Tuberculosis Spine in Bangladesh - Alam, Md Shafiul; Salam, Md Abdus; Farzana, Tayseer; Newaz, ASM Raushan; Islam, Md Saiful (Bangladesh Journal of Infectious Diseases, 2017)
Background: Spinal tuberculosis is more frequently reported in developing countries. Objective: The purpose of the present study was to see the socio-demographic characteristics of spinal tuberculosis patients. Methodology: This study was carried out in the Department of Neurosurgery, Dhaka Medical College Hospital during the period of January 2002 to December 2004 to elucidate the effectiveness of surgical and conservative treatment of the tuberculosis of the spine. For this purpose, a total number of 50 consecutive cases admitted during the study period with tuberculosis of the spine supported by investigations were included in this study. Result: The mean age of the patients was 25.4 years and ranged from 7 years to 68 years. The highest incidence of tuberculosis of the spine was found in age group between 11 to 20 years and 70% of the patients were under 30 years of age. Incidence of tuberculosis of this spine was more in male (62%) in comparison to female (3 8%) with a male female ratio of 1.63:1. In this study most of the patients came from low class society (66%) followed by middle class (28%) and high class (6%) respectively. Conclusion: Spinal TB more frequently occurs among the young age group with a male predominance. Bangladesh Journal of Infectious Diseases 2016;3(1):3-5